Kindergarten-Based Progressive Muscle Relaxation Training Enhances Attention and Executive Functioning: A Randomized Controlled Trial. Issue 3 (June 2022) - Jarraya, Sana; Jarraya, Mohamed; Engel, Florian A.
In the present study, we assessed the impact of kindergarten-based progressive muscle relaxation (PMR) on attention and executive functioning of 5–6-year-old children. In this randomized-controlled trial, 52 children (26 female; 26 male; M age = 5.4, SD = 0.2 years) from two private Tunisian kindergartens were randomly assigned to experimental and control groups. Over 12 weeks, 18 children performed PMR in two 30-minute sessions/week, another 17 children performed generic physical education (PE) for two 30-minute sessions/week, and 17 children in a control group (CG) had no systematically guided physical activity and engaged in usual self-chosen activities like free play or artisanal activities during kindergarten hours. Prior to (T0 ) and after (T1 ) the 12-week PMR intervention, all participants completed the Visuomotor Precision and Statue subtests of the Neuropsychological Evaluation Battery (NEPSY-2), the Teddy Bear Cancellation Test, and the Rey Simple Figure Test. Although there were no significant group differences at T0, repeated measures analysis of variance revealed higher scores for the PMR group relative to both the PE and CG groups on measures of attention, visuomotor precision, memory, and motor inhibition. PMR provided an effective relaxation technique and enhanced attention and executive functioning of these 5–6-year-old children, with important implications for assisting learning and academic achievement among young children.